The use of phytotherapy in the management of women in climacteric/menopause - Souza, Alciclei da Silva (2020)
The aim of the present study was to analyze the effects of the use of herbal medicines by healthy women on signs and symptoms of climacteric and menopause. This is an integrative review of literature, whose operationalization enables the synthesis of knowledge already produced in the period from January 2015 to December 2019, data collection was carried out through of the following virtual libraries: SciELO and VHL with access through the databases BDENF, LILACS and MEDLINE via PubMed. We analyzed 24 articles that have demonstrated that herbal medicines are effective for reducing the signs and symptoms vasomotor, neuropsychic, sexual dysfunction, urogenital changes and disorders metabolic diseases due to menopause. Among the most commonly used herbal medicines, it was observed that soy isoflavones, foeniculum vulgare, trigonella foenum-graecum and tribulus terrestris. The herbal medicines addressed showed significant results for the climatic complaints manifested in healthy women, in this way it can be a good therapeutic alternative for your specific treatment.